Modeling and Flow Analysis of Pure Nylon Polymer for Injection Molding Process - Nuruzzaman, D. M.; Kusaseh, N.; Basri, S.; A. N., Oumer; Zamzuri, Hamedon (IOP Publishing Ltd., UK, 2016)
In the production of complex plastic parts, injection molding is one of the most popular industrial processes. This paper addresses the modeling and analysis of the flow process of the nylon (polyamide) polymer for injection molding process. To determine the best molding conditions, a series of simulations are carried out using Autodesk Moldflow Insight software and the processing parameters are adjusted. This mold filling commercial software simulates the cavity filling pattern along with temperature and pressure distributions in the mold cavity. In the modeling, during the plastics flow inside the mold cavity, different flow parameters such as fill time, pressure, temperature, shear rate and warp at different locations in the cavity are analyzed. Overall, this Moldflow is able to perform a relatively sophisticated analysis of the flow process of pure nylon. Thus the prediction of the filling of a mold cavity is very important and it becomes useful before a nylon plastic part to be manufactured.